Does occurrence during sports affect sudden cardiac arrest survival?. (August 2019) - Pechmajou, Louis; Sharifzadehgan, Ardalan; Bougouin, Wulfran; Dumas, Florence; Beganton, Frankie; Jost, Daniel; Lamhaut, Lionel; Lecarpentier, Eric; Loeb, Thomas; Adnet, Frédéric; Agostinucci, Jean-Marc; Narayanan, Kumar; et al.
Abstract: Objectives: A higher survival rate was observed in Sudden Cardiac Arrest (SCA) occurring during sports activities, although the underlying mechanisms remain unclear. We tested the hypothesis that better initial management, rather than sports per se, may account for the observed better outcomes during sports activities. Methods: Data was taken between May 2011 and March 2016 from a prospective ongoing registry that includes all SCA in Paris and suburbs (6.7 million inhabitants). Sports-related SCA (i.e. SCA occurring during sport activities or within one hour of cessation of the activity) were identified. Results: Over the study period, 13, 400 SCA occurred, of which 154 were sports-related (median age: 51.2 years, 96.1% males). At discharge, sports activity was associated with an 8-times higher survival rate (39.7% vs. 5.1%, P < 0.001). Logistic regression showed that after considering potential confounders, including age, gender, SCA location, witness presence, time to response, and initial shockable rhythm, occurrence of SCA during sports was associated with a higher survival rate (OR 1.77, 95% CI 1.14–2.74, P = 0.01). However, after further adjustment for initial basic life support, i.e. bystander CPR and AED use, there was no association between sports setting and survival at hospital discharge (OR 1.43, 95% CI 0.91–2.23, P = 0.12). Conclusion: Sports-related SCA is a rare event, with an 8-times higher survival rate compared to non-sports-related SCA. Better initial management, including bystander CPR and AED use, rather than sports per se, mainly accounts this difference. This highlights the major importance of population education to basic life support in improving SCA outcome.